ANALISIS KINERJA KEUANGAN PADA PERUSAHAAN KULIT EXIS COLLECTION YOGYAKARTA - Tugimin Tugimin (Politeknik ATK Yogyakarta, 2014)
This study aims to determine the level of liquidity and profitability level of Company Exis Collection Yogyakarta. The data required are financial report includes the balances sheet and report of income in 2010 untill 2013. Methods of data collection using historical record, which is a methode of collecting data with recorded data of company which have a relations with a problem being studied. Analysed that used in this research is the analysis ratio methode, namely the ratio of liquidity analysis which includes: current ratio, cash ratio, quick ratio, working capital to total assets ratio and analysis of economic profitability ratio and profitability of their own capital. Based on the analysis of the results of the calculation of liquidity ratio and profitability ratio analysis, the results of the study can be summarized as follows : the ratio of liquidity which includes: current ratio, quick ratio, cash ratio and working capital Total Assets ratio at the Company Exis Collection Yogyakarta taken from the financial rerport of 2010 to 2013, showed an increase in the last 4 years. In 2013 the highest level of liquidity in the amount of 811%. The company's liquidity is considered good, because it is above the normal average standard of 200%. Profitability Ratio covering economic profitability and profitability of its own capital. Based on the overall calculation of economic profitability Company Exis Collection Yogyakarta in value either because the company still make a profit despite unstable and volatile in profit. Return on equity capital seen from the calculation as a whole for 4 years in general tend to rise and quite good because the company is still able to generate profits.